Numerical simulation of a microchip cooling wth microjet array - Yeo, Eng Soon; Mohd. Ghazali, Normah (Faculty of Mechanical Engineering, 2008)
The increasing demand for a more powerful microchip has projected power dissipation for high performance processor up to 300 Watts in 2018. With the dimensions expected to remain at 310 mm2, the heat density approaches the limit of conventional cooling methods. Microjet impingement cooling is a potential solution for the thermal management of these high performance microchips. This study looks into the numerical simulation of microjet arrays impinging with nozzle diameter ranging from 40 ?m to 76 ?m. Simulation results show the ability of a single-jet with 76 ?m diameter nozzle in cooling the microchip dissipating 4.3 Watts of heat flux over a 1 cmÂ² area. For multiple jets array, simulation results show that it is capable of achieving very low average surface temperature. It has also identified the problem associated with the increased number of jets due to the cross flow between the jets. It is found that multiple jets have better performance than the single jet even though the flowrate per jet is much lower.